Self-perception of body image and practices to correct it in adolescents from an educational institution, Lima, Peru - Enríquez Peralta, Raysa Emelin (2016)
Introduction. Adolescence is a stage of physical and psychological changes; body image is of special importance and dissatisfaction with this can contribute to inappropriate practices. Objective. To identify self-perception of body image and practices adopted to change it. Design. Mixed quantitative and qualitative study. Setting. Private education institution, Miraflores district, Lima. Participants. Male and female adolescents. Interventions. In 108 boys and girls for the quantitative study, and 48 for the qualitative study, weight and height, body image self-perception, in-depth individual and group interviews were obtained. Main outcome measures. Percentage of misperception of weight or height. Perception of body image and practices applied to modify this. Results. In this study 36.1% had misperception of their weight and 50.9% of their height. Although most respondents in the qualitative study revealed misperception, they showed apparent conformity with their bodies; those who did not show conformity with their body, expressed scornful comments; these and others (n=30) used diet, physical activity and medications to lose weight or to grow. Their parents and friends influenced heir decisions. 11- and 12-year-old participants were not interested in modifying their body image. Conclusions. Nearly one third of adolescents had misperception of their weight and half of them in regard to their height. Those not accepting their body image practiced activities to correct it.